Implementation of the Problem Based Learning Model to Improve Learning Outcomes in PPKN - Nuraeni Nuraeni; Selly Rahmawati*; Rian Nurizka; Isti Nurwidayanti (Riwayat: Educational Journal of History and Humanities, 2024)
The aim of this research is to determine the application of the problem-based learning model in PPKn subjects for class XI students at SMKN 2 Ciamis and how it can be improved. The research method used in this research is Kemmis and Taggart's Classroom Action Research model with planning, action, observation and reflection steps. The data collection used is tests and observations. The analytical technique used for analysis is descriptive statistics. The results of this research are that the application of the Problem Based Learning model can improve student learning outcomes in class XI citizenship education subjects from the research results. This can be seen from the level of completeness of student learning outcomes in the Iknown cycle at pretest of 41.66% and posttest of 66.6% and an increase in cycle II preetest of 81.6% and posttest of 83.3%. So the level of completeness of student learning outcomes from cycle I and cycle II has increased by 16.7%.